Perilaku Keuangan Generasi Z Berdasarkan Literasi Keuangan, Efikasi Diri, dan Gender: Studi Kasus Mahasiswa Perguruan Tinggi di Kota Jember - Efiatul Himmah; Retno Endah Supeni; Maheni Ika Sari (Jurnal Simki Economic, 2025)
A widely discussed topic today is financial behavior, especially the tendency for someone to think short-term and make impulsive purchases. This often causes financial problems, even for someone with adequate income, due to being less responsible in managing their finances. This study was conducted to evaluate the effect of financial literacy, self-efficacy, and gender differences on individual financial behavior in the Generation Z group, especially students of Jember City Colleges. This study uses a quantitative method with data collection techniques through questionnaires. The number of samples used was 398 respondents, selected using a purposive sampling technique. To analyze the relationship between the variables in this study, a multiple linear regression technique was used. The results of the multiple linear regression analysis showed that the three variables had a positive and significant effect on financial behavior. Financial literacy has a positive effect of 1.022, self-efficacy of 0.109, gender of 0.199 with a sig value of all variables of 0.00 or <0.05. The results of the analysis show that financial literacy, self-efficacy, and gender contribute to the financial behavior of students of Colleges in Jember City.